KEWENANGAN PEMERINTAH KOTA DENPASAR DALAM PEMBERIAN IZIN USAHA LAUNDRY - Agus Sastra Mahayana, I Komang; Wairocana, I Gusti Ngurah; Sudiarta, I Ketut (Kertha Semaya : Journal Ilmu Hukum, 2013)
The authority of the Government of Denpasar city in the granting permit of laundry business, carried out by the licensing agency up to its issuance as long as the business do not have a negative impact. As for the constraint and sanction to the perpetrator of laundry business without permit, this study is using the normative legal research method. While it is made easier to obtain the permit by the opening of Integrated Service Unit, still there are businesses running without permits, one of the reasons that causing a constraint for the perpetrator of business who does not process the permit is that the time consuming for processing the permit and the intricate bureaucracy. Meanwhile the constraint of the Government is that the lack of socialization continuously to appeal for the society to process the permit. Also by law it has been regulated regarding the sanction for the violation. The Government of Denpasar city has an authority in granting the laundry business permit around Denpasar as long as the business do not have a negative impact with the related agency that is the Licensing Agency and the constraint for the Government of Denpasar city in the issuance of the permit is that the lack of proactive action from the permit applicant so that complicate the Government in processing the permit.
Keywords: Autonomous Region, Authority, District/Municipal Government, Permit